Nanoparticle Detection of Urinary Markers for Point-of-Care Diagnosis of Kidney Injury. - Hyun Jung Chung; Kathryn L Pellegrini; Jaehoon Chung; Kamani Wanigasuriya; Innocent Jayawardene; Kyungheon Lee; Hakho Lee; Vishal S Vaidya; Ralph Weissleder (PLoS ONE, 2015)
The high incidence of acute and chronic kidney injury due to various environmental factors such as heavy metals or chemicals has been a major problem in developing countries. However, the diagnosis of kidney injury in these areas can be more challenging due to the lack of highly sensitive and specific techniques that can be applied in point-of-care settings. To address this, we have developed a technique called 'micro-urine nanoparticle detection (μUNPD)', that allows the detection of trace amounts of molecular markers in urine. Specifically, this technique utilizes an automated on-chip assay followed by detection with a hand-held device for the read-out. Using the μUNPD technology, the kidney injury markers KIM-1 and Cystatin C were detected down to concentrations of 0.1 ng/ml and 20 ng/ml respectively, which meets the cut-off range required to identify patients with acute or chronic kidney injury. Thus, we show that the μUNPD technology enables point of care and non-invasive detection of kidney injury, and has potential for applications in diagnosing kidney injury with high sensitivity in resource-limited settings.